If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1y + 2 = 16 + -8y Reorder the terms: 2 + -1y = 16 + -8y Solving 2 + -1y = 16 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 2 + -1y + 8y = 16 + -8y + 8y Combine like terms: -1y + 8y = 7y 2 + 7y = 16 + -8y + 8y Combine like terms: -8y + 8y = 0 2 + 7y = 16 + 0 2 + 7y = 16 Add '-2' to each side of the equation. 2 + -2 + 7y = 16 + -2 Combine like terms: 2 + -2 = 0 0 + 7y = 16 + -2 7y = 16 + -2 Combine like terms: 16 + -2 = 14 7y = 14 Divide each side by '7'. y = 2 Simplifying y = 2
| 180=60+60+x-20 | | X(x+2)=71 | | 5x+4=31-2x | | 10x+5(0)=10 | | (7y+8)-(6+6y)=10 | | -1y=0 | | 2a+5(a+4)(a+1)+9(a+4)(a+3)(a+1)= | | 6x+20-x=-4x+2 | | -1=0 | | 3z+2=A | | 0.03(2c-26)=-0.6(c-2) | | 7d+3=31 | | 32+15n=-20n-73 | | 6m+3=17 | | 3x+14=74+3x | | -1y=-2 | | 107=3x-4 | | 4x+1=80 | | 4x+8Y=692 | | -2x-36=6x+20 | | 5x^2*y^2-20xy= | | x^2-36=3x | | -1+5+-15+1+-2+5+1+-6= | | X+3x-6=90 | | 6x+2y=23.52 | | -8+15+-2+-15+-4+13+-17+11= | | 6k-3-2k=k-22 | | x*x-14x+33=0 | | -5=-2-3 | | -6z=3x | | x=-7+7 | | 7-8x=87-43x |